Boot up projects the Daily Telegraph guide to doing something useful with your computer - Maybury, Rick (Orion Business, 2000)
From producing newsletters and greeting cards, to lables and tables, faxing and emailing, to using your PC as a research tool, this work book provides help to anyone who wants to do more with their PCs beyond word processing and playing games.